2015
DOI: 10.1002/ep.12196
|View full text |Cite
|
Sign up to set email alerts
|

Solar radiation transfer and performance analysis for a low concentrating photovoltaic/thermal system

Abstract: In this study, we investigated a concentrating solar photovoltaic/thermal system that uses solar radiation in the visible and infrared ranges separately. In this system, photoelectric and photothermal conversions are achieved independently via the thermal unit and the photovoltaic (PV) module, respectively. The operation of the thermal unit is not affected by temperature limitations imposed by the PV module. The results indicate that water as the working fluid in the thermal unit directly absorbs 33% of the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…Working fluid optical properties are also optimized in their study. In another work, Zhao et al [58] demonstrated a CPV/T system [57]. Water is injected to cool the PV cells, and then a lesser amount of water flows via a thermal unit and absorbs infrared radiation.…”
Section: Liquid-cooled Pv/t Systemmentioning
confidence: 99%
“…Working fluid optical properties are also optimized in their study. In another work, Zhao et al [58] demonstrated a CPV/T system [57]. Water is injected to cool the PV cells, and then a lesser amount of water flows via a thermal unit and absorbs infrared radiation.…”
Section: Liquid-cooled Pv/t Systemmentioning
confidence: 99%
“…[10] created a mathematical model, which then analyzed the experimental performance of a solar chemistry system demonstrator. [11] Presented a photovoltaic/thermal (PV/T) design optimization system with both concentrated and concentrated solar radiations. [12] Studied the impact of the generation of high-scale photovoltaic on oscillation of the power system, which specifically considered inter-area oscillation.…”
Section: Introductionmentioning
confidence: 99%